Rehabilitation for balance impairment in patients after stroke: a single-blind randomized controlled study - Samardžić, Vesna; Jaganjac, Amila (Vojnosanitetski pregled, 2025)
Background/Aim. Balance problems in post-stroke patients should be recognized and treated with the most effective rehabilitation approaches. The aim of this study was to assess a group exercise program with chairs for improving balance and walking ability in post-stroke patients. Methods. This single-blind, randomized, controlled study included 86 post-stroke patients recruited from the only inpatient rehabilitation facility in the country. Patients were randomly assigned to one of the two groups: a group that had conventional rehabilitation only (control group) or a group that had a group exercise program with chairs, along with the conventional rehabilitation (treatment group). The methodology encompassed examination of demographics, history, clinical (balance was assessed using a Berg Balance Scale – BBS), and functional characteristics (walking ability and ability to use stairs). The assessments were made at baseline and after three weeks of rehabilitation. Results. All participants completed the exercise program. According to BBS, the balance improved in both examined groups: by 3.16 ± 2.16 (t = -4.989; p = 0.001) in the control group and by 8.33 ± 5.85 (t = -9.326; p = 0.001) in the treatment group. Significant improvement in balance and walking ability was registered in the treatment group compared to the control group. Conclusion. Group exercises with chairs appear to be effective in improving balance and stroke rehabilitation in post-stroke patients.
Keywords: core stability; physical and rehabilitation medicine; stroke; walking